Pengaruh Taraf Penyemprotan Air dan Lama Penyimpanan Terhadap Daya Tahan Ransum Broiler Finisher Berbentuk Pellet - Yuli Retnani; Edo Duanda Putra; Lidy Herawati (Agricultural Faculty, 2011)
The effect of different water spraying level and storage period on endurance of pellet broiler finisherABSTRACT. The storage is very important in a farm management, because this activity can take care of feed stability which enough and preferable to be consumed by animal and also strive for animal food availability continuously. The purpose of this research is to know the water spraying level and variation of storage period against the endurance of pellet broiler finisher ration. This research was designed by a Completely Randomized Design Factorial with two factors (water spraying different level and storage period) with four replicates, the significant result were analyzed by orthogonal contras test. On this experiment, the different level of water spraying (0, 3, 6%) were conducted during mixing at conditioning process, and then the ration were stored until four weeks to study the endurance of pellet e.g.: water content (%), water activity, specific gravity (ton/m3), pellet durability index (%), attack of insect. The water content, specific gravity, and pellet durability index was very significantly (P0.01) reduce by water spraying different level, and not significantly on water activity. The storage period showed very significantly (P0.01) increase the specific gravity, pellet durability index, and the insect attacks, and significantly (P0.01) decreased the water activity, but not effect on water content. Interaction among spraying level and storage period is very significantly (P0.01) on the values of water content, water activity, specific gravity and pellet durability.